2003
DOI: 10.1029/2001gc000274
|View full text |Cite
|
Sign up to set email alerts
|

Implications for crustal accretion at fast spreading ridges from observations in Jurassic oceanic crust in the western Pacific

Abstract: [1] Downhole logging data and basement stratigraphy interpretations are used to determine the spreading environment and crustal accretion history of the ocean basement cored at ODP Hole 801C located in the Jurassic Magnetic Quiet Zone of the western Pacific. High-resolution microresistivity data obtained with the Formation MicroScanner are used to measure the dip of the extrusive layers and indicate a 10°-30°i ncrease in dip down the drill hole with lava flow contacts dipping back toward the original ridge axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Four polarity changes are found within the upper, 150‐m, off axis lava sequence while two polarity changes are found within the lower lava sequence, which was presumably accreted at or near the spreading axis. Formation microscanner (FMS) log data show significant dips in the lava sequences within the hole [ Pockalny and Larson , 2003]. If the tilted lava sequence boundaries indicate that magnetization boundaries are similarly tilted, then changes in magnetic polarity can occur within a vertical hole [ Tivey et al , 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Four polarity changes are found within the upper, 150‐m, off axis lava sequence while two polarity changes are found within the lower lava sequence, which was presumably accreted at or near the spreading axis. Formation microscanner (FMS) log data show significant dips in the lava sequences within the hole [ Pockalny and Larson , 2003]. If the tilted lava sequence boundaries indicate that magnetization boundaries are similarly tilted, then changes in magnetic polarity can occur within a vertical hole [ Tivey et al , 2005].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies (Koppers et al, 2003;Pockalny and Larson, 2003) reinvestigated the basalt sections at Site 801 and divided them into an earlier-emplaced ''lower series'' (Sequences IV-VIII; >168 Ma) and a latererupted ''upper series'' (Sequences I-IV; $160 Ma), which is defined by the Lower Hydrothermal deposits (Sequence V) within Sequence IV. Those studies confirmed that there is a 10-Myr gap between the ''lower series'' and the ''upper series''.…”
Section: Geological Setting Sampling and Alteration Historymentioning
confidence: 98%
“…Constraints on magmatic accretion, mechanical deformation, and hydrothermal alteration processes are determined from the internal geologic structure of ophiolites [Moores and Vine, 1971;Penrose Conference Participants, 1972;Cann, 1974;Casey et al, 1981;Varga and Moores, 1985;Nicolas, 1989], marine seismic studies [Christeson et al, 1992;Detrick et al, 1993;Kent et al, 1994;Hallenborg et al, 2003], and limited deep crustal drilling [Alt et al, 1993;Pockalny and Larson, 2003;Tivey et al, 2005;Wilson et al, 2006]. Additional constraints come from studies of dike intrusion events [Delaney et al, 1998;Perfit and Chadwick, 1998], and eruptions along modern spreading centers [Soule et al, 2009, and references therein].…”
Section: Introductionmentioning
confidence: 99%